The Effectiveness of Using Games Two Truths and a Lie In Increasing Students’ Speaking Ability at SMP Labschool Untad Palu - Fauziah Rismauliani; Aminah Suriaman; Mashuri Mashuri; Abd Kamaruddin (MASI Mandiri Edukasi, 2025)
The study aimed to determine the effectiveness of using the